Longitudinal changes in disgust sensitivity during pregnancy and the early postpartum period, and the role of recent health problems - Dlouhá, Daniela; Roberts, S Craig; Hlaváčová, Jana; Nouzová, Kamila; Kaňková, Šárka (Scientific reports, 2023)
Disgust is an essential part of the behavioral immune system, protecting the individual from infection. According to the Compensatory Prophylaxis Hypothesis (CPH), disgust sensitivity increases in times of immunosuppression, potentially including pregnancy. We aimed to replicate a previous study observing longitudinal changes in disgust sensitivity in pregnant women. Additionally, for the first time, we explored how recent health problems influence these changes. To do this, we obtained disgust sensitivity measures from 94 women in each trimester and in early postpartum. In contrast to the original study, where disgust sensitivity was highest in the first trimester, we found that overall and animal reminder disgust increased across pregnancy and after birth. In line with the CPH, women who were recently sick in the first trimester had elevated disgust sensitivity at that time. Although disgust sensitivity was significantly higher in the second trimester and postpartum period compared to the first trimester in mothers pregnant with a male fetus, the overall results regarding the effect of fetus sex on disgust sensitivity were mixed. It seems that changing levels of disgust sensitivity during pregnancy and postpartum result from a suite of physiological and psychological changes that occur during this sensitive period of a woman's life.
Keywords: trimestry těhotenství; lidé; odpor; poporodní období; mužské pohlaví; porod; Pregnancy; Female; těhotné ženy; těhotenství; Male; Pregnant People; Pregnancy Trimesters; Parturition; ženské pohlaví; Disgust; Postpartum Period; Humans